Farmers knowledge, attitude and behavior in response to goods and services tax (GST) - Hassim, Nor Hidayah; Man, Norsida (IJAEB publisher, 2019)
Malaysia had officially replaced Sales and Services Tax (SST) to Goods and Services Tax (GST) since 1st April 2015. The changes lead to many responses but mostly are negative due to the lack of knowledge and information on GST. Agriculture output such as rice, vegetables, fruits, meats and eggs were categorized as zero-rated supply which they are free from GST. However, maintenances on the farm such as fertilizers, herbicides, ruminant feed, planting tools and others are in GST implementation. This shown the unbalance conditions by farmers as they are harvesting products which are free from GST but still pay GST in preparing them. Are the farmers suffered from such conditions? Thus, this study was undertaken to investigate on the farmers’ behavior in response to GST. Primary data were collected using structured questionnaire via face to face interview with 400 respondents from Kelantan, Kedah, Johor and Selangor. Majority of the respondents did not accept GST implementation in Malaysia (45.5%) followed by 33.5% were uncertain and 21% were accepted. Most of the respondents did not receive any information about GST information (64%). The perception level of respondents towards knowledge, attitude and behavior on GST implementation were moderate M=2.358, M=2.913 and M=2.818 respectively. The results showed by the three levels are mostly negative perceptions. The farmers should be provided with a clearer tax information, trainings and finance management for their survival on any new tax levied.